(untitled) (Dissertare, 2017)
This article analyzes how the synergy between the government, civil society and external agents allows proposing economic and social improvements in an indigenous community located in Amealco, Querétaro, Mexico. For this purpose, a theoretical approach to local development was made starting from the following question: How can the efforts of the government, the leaders of the indigenous communities and the local development agencies be articulated, to design proposals that allow the implementation of plans of economic and social development of the localities?. The study focused on identifying the forms of participation of different public and private actors in the experience of the Local Development Plan of the Community of San Ildefonso (State of Querétaro, Mexico), for which the model was used as a framework for analysis of local development of Prévost (1996). The research was based on the qualitative approach, applying the case study. The results show that overcoming the shortcomings is not yet perceptible for the entire population. However, valuable learning has been obtained and the foundations have been laid for the integral development of the community, given that the infrastructure, the media, the education system have been improved and progress has been made through the link with the Government sector.